Does the use of the dominant hand affect the direction of sinus extension to orient towards the right and left in pilonidal disease? - Kargın, Süleyman; Doğru, Osman; Turan, Ersin; Kerimoglu, Ramazan Saygin (The European Research Journal, 2021)
Objectives: The etiology of pilonidal sinus disease is still controversial. Acquired theory in its etiology has become more popular nowadays. The aim of this study was to investigate the effects of dominant hand use on sinus features and sinus direction. Methods: Eight hundred and sixty-five patients with diagnosis of primer pilonidal sinus disease were included. Data on patients’ ages, BMI, over-sitting histories, duration of disease, dominant hand use histories, the condition of their sinuses at the time of presentation, the number of sinus openings, sinus directions, and sinus extension directions were collected. Relationship was evaluated between dominant hand use and sinus direction or sinus extension direction. Results: There was no statistically significant difference between the patients’ ages, sexes, BMI figures, the durations of disease and over- sitting history and dominant hand use. While the sinus directions of patients who had shorter duration of disease were towards the midline, it was seen that as the duration of disease increased the sinus extensions were oriented any side (p = 0.01). There was, however, a significant relationship between the sinus extension direction and dominant hand use. It was observed that the sinus extension direction of the patients who dominantly used their right hands was towards the left, while the sinus extension direction of the patients with dominant left hands was towards the right (p = 0.04, RR:2.05). Conclusions: The fact that sinus extension directions can change against factors affecting body positions proves to be another factor which shows that pilonidal sinus disease is an acquired disease.